Reliability and validity of the Mentalization Questionnaire in a potentially depressed group of Chinese college students - Huang, Xin; Zhou, Zemin; Yang, Guang; Liu, Jiao; Li, Xuan; Li, Xuemei (Frontiers in Psychiatry, 2025)
PurposeMentalization, as a core psychosocial function, not only encompasses emotional regulation but also involves the perception and comprehension of one’s own and others’ emotional states, constituting a crucial capacity for establishing adaptive interpersonal relationships. University students, due to their unique challenges including academic competition, identity transition during this critical developmental period, and social pressures, demonstrate that impairments in mentalization capacity may significantly elevate the risk of depressive disorders. Concurrently, the exacerbation of depressive symptoms can further compromise mentalization functioning, thereby creating a self-perpetuating pathological cycle.However, there is a lack of validated assessment tools for mentalization in China. This study aims to provide a validated instrument for assessing mentalization in the Chinese population.MethodsThe Chinese version of the Mentalization Questionnaire (MZQ) was developed through rigorous cross-cultural adaptation procedures. Following Brislin’s translation model, medical English experts initially translated the instrument into Chinese. Subsequently, a panel of specialists in psychology and psychiatry conducted comprehensive reviews, back-translation, and iterative revisions to ensure conceptual equivalence. The finalized scale was administered to 874 Chinese university students exhibiting subthreshold depressive symptoms (Patient Health Questionnaire-9 [PHQ-9] score ≥10). Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were sequentially implemented to establish and verify the factorial structure. Concurrent validity was examined using the 8-item Reflective Functioning Questionnaire (RFQ-8). To assess test-retest reliability, 85 participants were randomly selected for retesting one week after initial administration.ResultsThe MZQ revealed a 3-factor structural model, and confirmatory factor analysis showed satisfactory fit indices for all three structures (χ²/df = 3.69, NFI = 0.83, CFI = 0.87, GFI = 0.92, IFI = 0.87, TLI = 0.83, RMSEA = 0.078). The correlation coefficient between the total MZQ score and the RFQ-C (Certainty about mental states) was -0.557, while the correlation coefficient between the total MZQ score and the RFQ-U (Uncertainty about mental states) was 0.428.ConclusionThe Chinese version of the Mentalization Questionnaire (MZQ) demonstrates good validity and reliability, making it a suitable tool for assessing mentalization levels among college students with potential depressive symptoms.